DRYING KINETICS OF WEST INDIAN CHERRY: INFLUENCE OF OSMOTIC PRETREATMENT - SILVA, MIRTES APARECIDA DA CONCEIÇÃO; CÔRREA, JEFFERSON LUIZ GOMES; DA SILVA, ZAQUEL ERNESTO (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2011)
The purpose of this work was to study the influence of osmotic pretreatment on the convective drying kinetics of the West Indian cherry (Malpighia emarginata DC). Osmotic dehydration was performed with a 65ºBrix sucrose solution at room temperature, having the fruits immersed for 4 or 12 hours, using a 1:10 proportion of fruit:solution (w:w). After the osmotic dehydration, the fruits were convectively-dried at 50ºC on a tray dryer. The convection drying was modeled based on Fick’s second law, while the effective mass diffusion (Def) was determined using Levenberg-Marquardt’s minimization algorithm by means of the paradigm of inverse methods. The values of effective mass diffusion coefficients observed were in the same order of magnitude as those reported in the literature. The condition that promoted the highest value of diffusivity was convective drying preceded by 4 hours of osmotic dehydration. This condition was also the one with the best fit agreement of the tested model.